2002
DOI: 10.1021/jm0200916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Potent Leukotriene A4 Hydrolase Inhibitors. Identification of 3-[Methyl[3-[4-(phenylmethyl)phenoxy]propyl]amino]propanoic Acid

Abstract: Leukotriene B(4) (LTB(4)) is a potent, proinflammatory mediator involved in the pathogenesis of a number of diseases including inflammatory bowel disease, psoriasis, rheumatoid arthritis, and asthma. The enzyme LTA(4) hydrolase represents an attractive target for pharmacological intervention in these disease states, since the action of this enzyme is the rate-limiting step in the production of LTB(4). Our previous efforts focused on the exploration of a series of analogues related to screening hit SC-22716 (1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…In contrast, recent work by Funk's group showed that 5-LO deficiency did not affect the formation of lipid-rich lesions in apoE deficient mice [39]. More recently, we used a selective LTA 4 H inhibitor, SC-57461A [40,41], at a dose of 30 mg/kg twice per day subcutaneously in the apoE deficient mice with CAL and treated with Ang II. Consistent with Funk's report, our results also showed that a LTA 4 H inhibitor failed to attenuate ligation-induced vascular remodeling in apoE deficient mice (Fig.…”
Section: Impact Of Pro-inflammatory Factors On Neointimal Hyperplasiamentioning
confidence: 90%
“…In contrast, recent work by Funk's group showed that 5-LO deficiency did not affect the formation of lipid-rich lesions in apoE deficient mice [39]. More recently, we used a selective LTA 4 H inhibitor, SC-57461A [40,41], at a dose of 30 mg/kg twice per day subcutaneously in the apoE deficient mice with CAL and treated with Ang II. Consistent with Funk's report, our results also showed that a LTA 4 H inhibitor failed to attenuate ligation-induced vascular remodeling in apoE deficient mice (Fig.…”
Section: Impact Of Pro-inflammatory Factors On Neointimal Hyperplasiamentioning
confidence: 90%
“…LTB4 is a potent proinflammatory lipid mediator synthesized by cells of the immune system and stimulates the production of several cytokines [10]. LT synthetic route is known to have three critical factors.…”
Section: Introductionmentioning
confidence: 99%
“…LTD4 is then cleaved by dipeptidases to form LTE4. Finally, the third factor is related to the activity of LTA4 hydrolase (LTA4H), which generates LTB4 by hydrolysis of LTA4 [10, 11]. LTA4H activity is known to be exerted by two bifunctional zinc metalloenzymes, EC 3.3.2.6, the canonical LTA4H [12], and EC 3.4.11.6 (basic aminopeptidase) [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…A LTA 4 hidrolase é uma enzima ubíqua (GRICE et al, 2008;HAEGGSTRÖM;THOLANDER;WETTERHOLM, 2007;MURPHY e GIJÓN, 2007) altamente específica para o LTA 4 , convertendo-o a LTB 4 (HAEGGSTRÖM; THOLANDER; WETTERHOLM, 2007;MURPHY e GIJÓN, 2007;PENNING et al, 2002). O LTB 4 é produzido por diversas células imunocompetentes, como neutrófilos e macrófagos, estimula diversas citocinas (PENNING et al, 2002), ativa células inflamatórias, como neutrófilos, macrófagos, células T e B (GRICE et al 2008;KIRKLAND et al, 2008), e é um mediador inflamatório potente que amplifica diversas doenças inflamatórias, como a AR (GRICE et al 2008;LIANG et al, 2007;PENNING et al, 2002).…”
Section: A Apb E a Inflamaçãounclassified
“…Devido à grande importância do LTB 4 em estados inflamatórios, diversos estudos buscam um inibidor seletivo para a LTA 4 hidrolase (GRICE et al, 2008;KIRKLAND et al, 2008;PENNING et al, 2002). Apesar da importância da atividade LTA4 hidrolase em processos inflamatórios, a atuação dessa atividade na artrite não será abordada no presente trabalho, pois a medida dessa atividade envolve outra metodologia (HPLC) e outros reagentes específicos e de custo vultoso.…”
Section: A Apb E a Inflamaçãounclassified